G356 Teachers' experiences of working with children with Autism and sensory processing needs. (7th April 2014) - Barrett, E; Ayyash, H; Waltz, M; Waltz, M; Banerjee, S
Abstract : Aims: The purpose of this project was to investigate teachers' perceptions of their experiences of the Sensory Processing Pathway for children with a diagnosis of autism, identifying strengths and limitations and outcomes to guide service development. Methods: Four teachers of children with a diagnosis of autism who had received input through the sensory processing care pathway completed questionnaires. One participant also completed a semi-structured qualitative interview. Numerical data analysis was completed of descriptive and comparative data, and key messages were highlighted in qualitative data. Results: Results showed there to be a decrease in undesirable behaviours which could be perceived to impact negatively upon the child's ability to engage in school activities, and also an increase in desirable behaviours following the application of sensory processing principles in practice. Negative impacts of ongoing sensory processing needs upon the children's ability to engage in school activities were indicated by teachers to reduce in frequency following the application of sensory processing principles in practice. Conclusion: This study, when considered alongside existing studies investigating the impacts of applying sensory processing principles to practice on functional performance of daily activities in children with a diagnosis of autism, strengthens the belief that it is beneficial to apply sensory integration principles to practice when working with children with a diagnosis of autism who may be experiencing difficulties with functional performance of daily activities in mainstream school.